IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY USING CUE CARDS - Sahliya Azizah Efendi; Meisuri - (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACTThis study concerns on improving students’ achievements and to find out whether the cue cards can improve the students’ achievement in writing descriptive text. This study was conducted by using Classroom Action Research. The subject and population of this study is the second grade VIII-2 students of SMP Negeri 1 Padang Bolak. The number of the subject was 36 students, consisting of females and males. This procedure of this research was administrated in two cycle and six meetings. The qualitative data were taken from diary notes and observation sheet. The quantitative data were taken from the mean of the students’ score in writing test. Based on the data analysis, the students’ score got improvement in every cycle. In the First Test , the mean of the students’ scores was 52.22 while in Second Test, the mean of the students’ scores was 64.44 and in Third Test, the mean of students’ scores was 75.55. The qualitative data showed that students’ was interested in the using of Cue Card as a media in teaching learning process. The conclusion is that the using of Cue Cards as a media in teaching significantly improved students achievement in writing descriptive text and also impressed the students’ enthusiasm in doing the group work of Cue Cards media to make a text and to express their idea well.Keywords: achievement, writing, descriptive, cue cards